The impact of investment in innovation on productivity: Firm-level evidence from Ireland - Mattia Di Ubaldo; Iulia Siedschlag (The Economic and Social Research Institute (ESRI), 2017)
This paper examines the relationship between investment in innovation and productivity across firms in Ireland. We estimate a structural model using information from three linked micro data sets over the period 2005-2012 and identify the relationships between investment in innovation, innovation outputs and productivity. Our results indicate that innovation is positively linked to productivity. This result holds for all types of innovation and for both R&D and non-R&D expenditures. The innovation-related productivity gains range from 16.2 per cent to 35.4 per cent. The strongest link between innovation and productivity is found for firms with R&D spending and with product innovation.
Keywords: F10; F23; O31; 330; Investment in innovation; innovation outputs; productivity; firm heterogeneity